2023
DOI: 10.3390/buildings13041046
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity and Mechanical Properties of Cement Slurries Containing Titanium Dioxide

Abstract: The effect of titanium dioxide (TiO2) on the mechanical properties of cement slurries including their benefits on air purification and abatement of pollutants is not well documented. Cementitious-based slurries are typically applied in thin layers as decorative coatings for existing facades, protection against an ingress of aggressive ions, or rainproof covers to minimize water penetration. Different parameters including the TiO2 concentration, dispersion time during batching, and applied thickness on top of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…Based on Figure 10a, the compositions with TiO2 exposed to the external conditions representing outdoor environments (receiving direct sunlight radiation) had higher final lightness values when compared to the control groups, as expected and similarly to other studies [4,6,15,68], except for photocatalytic mortars produced with a 1:4 cement:sand ratio. Thus, although RhB may experience a dye-sensitized photoreaction [69], the increased results when in the presence of the photocatalyst probably demonstrate the occurrence of the catalytic process.…”
Section: First Stage Of Color Change Analysis: External Exposuresupporting
confidence: 87%
See 3 more Smart Citations
“…Based on Figure 10a, the compositions with TiO2 exposed to the external conditions representing outdoor environments (receiving direct sunlight radiation) had higher final lightness values when compared to the control groups, as expected and similarly to other studies [4,6,15,68], except for photocatalytic mortars produced with a 1:4 cement:sand ratio. Thus, although RhB may experience a dye-sensitized photoreaction [69], the increased results when in the presence of the photocatalyst probably demonstrate the occurrence of the catalytic process.…”
Section: First Stage Of Color Change Analysis: External Exposuresupporting
confidence: 87%
“…Overall, in the three types of compositions with TiO 2 addition, the fresh state density was higher than the control samples without the photocatalyst. This behavior was also observed in another study by Jabali et al [4]: when TiO 2 content increased, the fresh density values of mortars were also higher. This assertion finds support in the research of Naganna et al [48], who concluded that TiO 2 nanoparticles serve as effective nanofillers, enhancing the concrete's resistance to water permeability.…”
Section: Characterization Of the Mortarssupporting
confidence: 85%
See 2 more Smart Citations
“…In examining Table 9 and Figure 11b, the 90-day RFS values post-exposure to 800 In examining Table 9 and Figure 11b, the 90-day RFS values post-exposure to 800 exhibited a decrease of 72.04% in the R0 control example, 61.46% in the R1 sample, b tween 60.25% and 61.84% in the YP-doped R2-R4 examples, and between 61.20% a 63.75% in the RP-doped R5-R7 examples. Comparing the YP and RP-added mortar exa ples, YP demonstrated a superior filler effect due to its finer grain size, marginally enhan ing RFS capacities compared to RP [61][62][63]. Furthermore, akin to the RCS results, utilizi YP and RP at 1% and 3% levels enhanced the RFS capacity of the samples by over 5%.…”
Section: Residual Flexural Strengthmentioning
confidence: 91%